2000
DOI: 10.1002/(sici)1099-1085(200001)14:1<117::aid-hyp914>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Using synthetic flow duration curves for rainfall-runoff model calibration at ungauged sites

Abstract: Abstract:The primary objective of the study is to propose a strategy for rainfall±runo model calibration at ungauged sites. This strategy comprises two main components: (1) development of the regional analysis method to synthesize the¯ow duration curves at ungauged sites; and (2) utilization of the synthetic¯ow duration curves for model calibration. Since the regional analysis method can synthesize the¯ow duration curves at ungauged sites, the continuous rainfall±runo model coupled with a global optimization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 17 publications
0
51
1
1
Order By: Relevance
“…FDCs have been used previously in model calibration and evaluation (Blazkova and Beven, 2009;Son and Sivapalan, 2007;Sugawara, 1979;Yu and Yang, 2000). The novel aspect of our use of the FDC is that it takes account of uncertainty in the discharge data and at the same time shows that the FDC can work surprisingly well as a single criterion in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FDCs have been used previously in model calibration and evaluation (Blazkova and Beven, 2009;Son and Sivapalan, 2007;Sugawara, 1979;Yu and Yang, 2000). The novel aspect of our use of the FDC is that it takes account of uncertainty in the discharge data and at the same time shows that the FDC can work surprisingly well as a single criterion in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Calibration approaches that do not rely on direct time-series versus time-series comparison are useful in such situations. Prior approaches to model calibration without direct time series comparison include calibration to spectral properties (Montanari and Toth, 2007), recession curves (Winsemius et al, 2009), slope of the flow-duration curve (Yadav et al, 2007;Yilmaz et al, 2008), base-flow index (Bulygina et al, 2009) and the use of a performance measure based on specified exceedance percentages of a synthetic regional flow-duration curve (FDC) for calibration at un-gauged sites (Yu and Yang, 2000). However, in these studies uncertainties in observed discharge are not considered explicitly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawbacks of this methodology are: the great number of parameters to be regionalized, the correlation between parameters, the difficulty of associating parameters with catchment characteristics and the existence of multiple sets of parameters providing reasonably satisfactory results (Vogel 2006). Yu and Yang (2000) suggested a methodology for hydrological models calibration using synthetic FDCs. The main idea is to find a set of parameters able to synthetize the ranked flows, with no obligation to reproduce their serial structure (Pinheiro and Naghettini 2010).…”
Section: Indirect Calibration Using Synthetic Fdcsmentioning
confidence: 99%
“…Smakhtin's recent review (2001) documents the use of FDCs in low-flow hydrology. Recent applications include: studies of the impact of land-use/cover change on streamflow from paired catchment studies Croker et al, 2003;Lane et al, 2003), regionalisation studies (Fennessey & Vogel, 1990;Meunier, 2001); and in prediction for ungauged basins (Yu & Yang, 2000;Holmes et al, 2002;Yu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%